2004
DOI: 10.1136/ijgc-00009577-200403000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A new prognostic model comprising p53, EGFR, and tumor grade in early stage epithelial ovarian carcinoma and avoiding the problem of inaccurate surgical staging

Abstract: Abstract. Epithelial ovarian carcinoma rarely occurs because of a single event. Therefore, no single biological tumor factor will give accurate prognostic information for all ovarian cancer patients. On the other hand, a combination of two or more independent factors may yield an improved overall prognostic index. Because FIGO stage is included in most of the previously presented models, inaccurate surgical staging in patients with apparently early disease has been a problem. In a series of 226 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Positivity for p27 was detected in 57% of the tumors, and this finding is consistent with positivity of 33% to 72% demonstrated in previous studies. 20 Positive staining for C-MYC was detected in 76% of tumors in our study, and this result could be compared with 66% positivity for C-MYC in a study from Chen et al 21 In agreement with prior ovarian 14,16 carcinoma studies, p53 positivity was correlated with worsening tumor grade and in disagreement with findings from the Gynecologic Oncology GroupY157 cohort study on high-risk, early-stage EOC. 2 Furthermore, poorly differentiated tumors usually stained positively for p27 alone as well as concomitantly for p53 and p27 in our study.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Positivity for p27 was detected in 57% of the tumors, and this finding is consistent with positivity of 33% to 72% demonstrated in previous studies. 20 Positive staining for C-MYC was detected in 76% of tumors in our study, and this result could be compared with 66% positivity for C-MYC in a study from Chen et al 21 In agreement with prior ovarian 14,16 carcinoma studies, p53 positivity was correlated with worsening tumor grade and in disagreement with findings from the Gynecologic Oncology GroupY157 cohort study on high-risk, early-stage EOC. 2 Furthermore, poorly differentiated tumors usually stained positively for p27 alone as well as concomitantly for p53 and p27 in our study.…”
Section: Discussionsupporting
confidence: 60%
“…20 In previous studies on patients in FIGO stages IYII, positive staining for p53 was found in 29% to 51% of the tumors. 1,2,15,16 As some patients with p53-positive tumors continued to survive and some patients with p53-negative tumors died of their disease, some more molecular markers are needed for better prognostic tools. Therefore, analysis of p27 and C-MYC, important regulators of the apoptosis, was performed and added to p53, and their relation to clinicopathological factors was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As p53 overexpression is more likely found in tumors with increased amounts of residual disease, and in disseminated disease, it may be indicative of a more aggressive nature in p53‐positive tumors. The fact that only three tumors were found to be p53 negative in this study was not surprising as p53 overexpression is observed more frequently in serous tumors than in any other histologic subtypes (8,10,21,23,25) , with serous type being associated with moderate to high p53 expression (9) , and this study also has a higher number of patients presenting with advanced‐stage disease.…”
Section: Discussionmentioning
confidence: 56%
“…10,15 In previous studies on patients with FIGO stages I to II, positive staining for p53 was found in 29% to 51% of the tumors. 1,10,11,15 The frequency of PTEN expression for ovarian cancer is inconsistent between the studies. Kurose In the present study, positive staining of tumors for p53 was correlated to some clinicopathologic parameters as tumor grade in the total series, but not in the subgroup of serous tumors.…”
Section: Discussionmentioning
confidence: 99%